The performance of Boer goats browsing Leucaena leucocephala in KwaZulu-Natal, South Africa - Morris, C.D.; Toit, L.P. du (1998)
The introduction of mimosine detoxifying microbes to the rumen of African livestock eliminates the need to restrict the levels of Leucaena leucocephala in their diet to avoid mimosine toxicity. The performance of weaned Boer goats, which were inoculated with mimosine-detoxifying microbes, browsing stands of both L. leucocephala cv. Cunningham and var. Spectra was studied over 2 seasons. Goats were stocked at 8.6, 15 and 20 goats/ha for 120 days in 1994-95, and 11.5,15, and 20 goats/ha for 140 days in 1995-96. No obvious signs of mimosine toxicity were visible during the trial. Weight gains were positive, except during the period immediately after the goats were introduced to the trial in 1994 and after short periods off the trial in the mid-summer of both seasons, necessitated by drought- and hail-induced defoliation of the leucaena trees. The mean individual animal performance over both years and leucaena types was 87.6.4 g/d, with gains approaching 200 g/d at times. There were no differences (P>0.05) in gain per animal between leucaena types or stocking rates. Therefore, gain per hectare increased with increasing stocking rate, resulting in a significantly (P